Tasks and impact of school social work in Switzerland as perceived by teachers, principals and school social workers – a multilevel analysis - Werner Wicki; Roland Künzle; Marianne Mueller; Uri Ziegele; Karin Stadelmann; Kurt Gschwind (International Journal of School Social Work, 2020)
To investigate whether the perceptions of school-based professionals regarding the tasks and impact of school social work (SSW) converge or diverge, this study collected survey data among 638 teachers, 41 school social workers, 62 principals, and 23 special education teachers distributed over 92 Swiss schools. After constructing several scales measuring the tasks and the impact of SSW via principal factor analyses, ANOVA’s were carried out to compare the mean perceptions of the included professionals. To prove for related perceptions between teachers and school social workers multilevel analyses were performed by including additional exploratory variables such as school context and personal factors. Most results indicate considerable concordance between the professions included in the study regarding the tasks rated as important as well as with respect to the outcomes of school social work. While all professions agreed that social problem solving, i.e. the intervention approach, is the most important approach of school social work, some discordance was found with respect to preventive tasks such as project work. Overall, teachers and principals tended to underestimate the effects of school social work implying some potential to destabilize their collaboration with the school social workers. While the multi-level analyses revealed a high variability between schools due to local factors, the perceptions of the teachers and the school social workers located at the same schools proved to be independent over most investigated dimensions.
Keywords: school social work; task; impact; teacher